Whole Transcriptome Analysis of Notochord-Derived Cells during Embryonic Formation of the Nucleus Pulposus - Peck, Sun H. (Sci Rep, 2017)
Recapitulation of developmental signals represents a promising strategy for treating intervertebral disc degeneration. During development, embryonic notochord-derived cells (NDCs) are the direct progenitors of cells that populate the adult nucleus pulposus (NP) and are an important source of secreted signaling molecules. The objective of this study was to define global gene expression profiles of NDCs at key stages of embryonic disc formation. NDCs were isolated from Shh-cre;ROSA:YFP mice at embryonic day 12.5 and postnatal day 0, representing opposite ends of the notochord to NP transformation. Differences in global mRNA abundance across this developmental window were established using RNA-Seq. Protein expression of selected molecules was confirmed using immunohistochemistry. Principal component analysis revealed clustering of gene expression at each developmental stage with more than 5000 genes significantly differentially expressed between E12.5 and P0. There was significantly lower mRNA abundance of sonic hedgehog pathway elements at P0 vs E12.5, while abundance of elements of the transforming growth factor-beta and insulin-like growth factors pathways, and extracellular matrix components including collagen 6 and aggrecan, were significantly higher at P0. This study represents the first transcriptome-wide analysis of embryonic NDCs. Results suggest signaling and biosynthesis of NDCs change dramatically as a function of developmental stage.